Translating the Developmental Origins of Health and Disease concept to improve the nutritional environment for our next generations: a call for a reflexive, positive, multi-level approach. (17th December 2018) - McKerracher, L.; Moffat, T.; Barker, M.; Williams, D.; Sloboda, D. M.
Abstract: Evidence supporting the Developmental Origins of Health and Disease (DOHaD) hypothesis indicates that improving early life environments can reduce non-communicable disease risks and improve health over the lifecourse. A widespread understanding of this evidence may help to reshape structures, guidelines and individual behaviors to better the developmental conditions for the next generations. Yet, few efforts have yet been made to translate the DOHaD concept beyond the research community. To understand why, and to identify priorities for DOHaD Knowledge Translation (KT) programs, we review here a portion of published descriptions of DOHaD KT efforts and critiques thereof. We focus on KT targeting people equipped to apply DOHaD knowledge to their everyday home or work lives. We identified 17 reports of direct-to-public DOHaD KT that met our inclusion criteria. Relevant KT programs have been or are being initiated in nine countries, most focusing on secondary school students or care-workers-in-training; few target parents-to-be. Early indicators suggest that such programs can empower participants. Main critiques of DOHaD KT suggest it may overburden mothers with responsibility for children's health and health environments, minimizing the roles of other people and institutions. Simultaneously, though, many mothers-to-be seek reliable guidance on prenatal health and nutrition, and would likely benefit from engagement with DOHaD KT. We thus recommend emphasizing solidarity, and bringing together people likely to one day become parents (youth), people planning pregnancies, expecting couples, care workers and policymakers into empowering conversation about DOHaD and about the importance and complexity of early life environments.